Screening for neonatal sepsis by determination of C-reactive protein at a pediatric hospital in Peshawar, Pakistan - Ahmad, Irshad (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
In developing countries such as Pakistan, mortality from neonatal sepsis is higher than that in developed countries. Without specific and sensitive biomarkers of infection and reliable interpretation of available biomarkers, embarking on antibiotic therapy is still largely dependent on clinical judgment. In neonates the blood concentration of C-reactive protein (CRP) escalates within 4 to 6 hours of an infectious episode, becomes abnormal by 24 hours and peaks at around 48 hours. Hence, CRP levels can be exploited as a biomarker for neonatal sepsis. To determine the accuracy of CRP for diagnosing neonatal sepsis at a pediatric hospital in Peshawar, Pakistan. The study setting was Department of Pediatrics at Lady Reading Hospital, Peshawar, Pakitan over six months (10th October 2013-20th April 2014). A total of 169 suspected neonates having sepsis were tested for CRP levels; blood culture was also done to confirm the findings on CRP levels. Study neonates had a mean age of 12.3 ± 7.3 days and most (52.7%) were aged up to 10 days. The gender ratio of neonates was 54.4% male to 45.6% female. There were positive CRP results for 81 (47.9%) neonates and negative CRP results for 88 (52.1%) neonates. Based on blood cultures, sepsis was detected in 60 (35.5%) neonates and was negative in 109 (64.5%) neonates. CRP determination had specificity of 75.2% and sensitivity of 90%, and had positive and negative predictive values of 66.7% and 93.2%, respectively. CRP blood concentration is an accurate tool for high sensitivity detection of neonatal sepsis with acceptable specificity.